Gold, platinum, and expected stock returns - Huang, Darien; Kilic, Mete (Journal of Financial Economics, 2019)
The ratio of gold to platinum prices (GP) reveals persistent variation in risk and proxies for an important economic state variable. GP predicts future stock returns in the time series, explains stock return variation in the cross-section, and is significantly correlated with option-implied tail risk measures. Contrary to conventional wisdom, gold prices fall in recessions, albeit by less than platinum prices. A model featuring recursive preferences, time-varying tail risk, and preference shocks for gold and platinum can account for asset pricing dynamics of equity, gold, and platinum markets, rationalize the return predictability, and explain why gold prices fall in bad times.